Mapping social impacts of agricultural commodity trade onto the sustainable development goals - Schaafsma, M.; Dreoni, I.; Ayompe, L.M.; Egoh, B.N.; Ekayana, D.P.; Favareto, A.; Mumbunan, S.; Nakagawa, L.; Ngouhouo-Poufoun, J.; Sassen, M.; Uehara, T.K.; Matthews, Z. (Wiley, 2023)
While international trade in agricultural commodities can spur economic development especially where governance is strong, there are also concerns about the local impacts of commodity production and their distribution on the environment and on people. The sustainable development goals (SDGs), though seeing trade as a means to support their achievement, recognise the need to address potential negative social and environmental impacts. It is therefore important to assess the contribution of international trade to the SDGs in commodity production areas. The environmental impacts of commodity production are widely acknowledged, but much less is known about its social impacts, and how this affects poverty reduction objectives across different dimensions. Impacts on human wellbeing and equity depend on a multitude of factors, including resources, systemic conditions and outputs of production. Through a broad literature review on soy, coffee, cocoa and palm oil, we show how studies have addressed different aspects of these factors and their impacts. The paper demonstrates how efforts by actors in global supply chains are related to a large number of SDGs and their targets. We link the social impacts and factors to the SDGs and a list of potential indicators and variables to guide operationalisation of assessments in new empirical studies.